2021
DOI: 10.3389/fcomm.2021.707391
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Literacy Linked to Attitudes Toward COVID-19 Vaccinations: A Pre-Registered Study

Abstract: The ongoing COVID-19 pandemic, which began in early 2020, is a global public health crisis. To prevent the spread of COVID-19, it is necessary to promote vaccine administration and preventive behaviors (e.g., mask, handwashing, social distancing). However, some people have negative attitudes toward vaccine administration and preventive behaviors. Based on the information-deficit model, the present study investigated how scientific literacy and perceived understanding of COVID-19 are associated with attitudes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
2
17
1
2
Order By: Relevance
“…We also found that attitudes and motivated beliefs appeared to play a role in people’s predictions and explanations regarding COVID-19, consistent with other recent reports in the literature (e.g., Motoki et al, 2021 ; Sanchez and Dunning, 2021 ; Thoma et al, 2021 ). In the current data, trust in medical science and taking the COVID-19 disease seriously were predictive of people’s accuracy in explaining the disease, as well as their understanding of vaccines and with wanting to be vaccinated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that attitudes and motivated beliefs appeared to play a role in people’s predictions and explanations regarding COVID-19, consistent with other recent reports in the literature (e.g., Motoki et al, 2021 ; Sanchez and Dunning, 2021 ; Thoma et al, 2021 ). In the current data, trust in medical science and taking the COVID-19 disease seriously were predictive of people’s accuracy in explaining the disease, as well as their understanding of vaccines and with wanting to be vaccinated.…”
Section: Discussionsupporting
confidence: 91%
“…(Interestingly, they found that simply knowing COVID-19 symptoms did not correlate with precautionary behaviors.) It is also consistent with Motoki et al (2021) , who found that scientific literacy was linked to attitudes toward COVID-19 vaccinations, and Sanchez and Dunning (2021) , who found that attitudes regarding scientists predicted COVID-19 attitudes and protective behaviors even more than did political partisanship.…”
Section: Discussionsupporting
confidence: 84%
“…Further, students felt like they could make an informed decision regarding vaccination after the completion of the module ( Table 1 ). Given perception of vaccination ( 15 , 19 , 20 ) and information levels ( 24 , 25 ) are related to vaccine-acceptance, this would suggest that student's plans to get vaccinated may have shifted due to the module.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance is the rampant vaccine mistrust to be higher among non-white and non-male demographic groups ( 20 23 ). Furthermore, both lower education and information levels were found to be correlated with lower willingness to get vaccinated and to abide by preventive measures ( 24 , 25 ). Such diverse population of individuals include non-STEM majors (henceforth called “non-majors”) college students who may depend on a college science curriculum to enhance their scientific literacy ( 26 ).…”
Section: Introductionmentioning
confidence: 98%
“…For example, Chen et al used Protection Motivation Theory to explain the association between COVID-19 knowledge and adoption of preventive behaviors, including intention to get vaccinated ( Chen et al, 2021 ). Motoki et al used the information-deficit model to examine whether scientific literacy and perceived level of knowledge about COVID-19 are associated with attitudes toward COVID-19 vaccinations and preventive behaviors ( Motoki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%